Teknologi og tværfaglighed: en analyse af diskussionen omkring indførelse af EPJ på en hospitalsafdeling - Morten Schnack (Copenhagen Business School (CBS), 2008)
– The aim of this thesis is to analyse how the implementation of electronic patient records (EPR) may affect cross-disciplinary clinical practice in a particular hospital department. The thesis presents a modified discourse analysis, a technology analysis, and some reflections on power. Using nineteen interviews of doctors and nurses in the Paediatric Department of Hvidovre Hospital, it emphasizes those actions in relation to the implementation of EPR that may either hinder or foster cross-disciplinary co-operation between doctors and nurses. The general pattern is that EPR fosters mono-disciplinarity, even though the management's ambitions in regard to EPR had been to foster crossdisciplinarity. The overall conclusion of the thesis is that EPR has the capacity to open a space for cross-disciplinarity. The changes in the documentation practices of the doctors and the nurses that follow from the implementation of EPR have also brought changes in their communication and decision-making processes. This can be seen especially when they prepare for regular rounds, during rounds, and in the subsequent documentation of rounds. Also, the changes in both the structures of communication and the processes of decision-making do not seem to result in fundamental task slippage between the doctors and the nurses because the doctor maintains ultimate authority and responsibility in regard to diagnosis, prescriptions, and treatment plans, while the nurses remain responsible for patient care (nursing) and keeping the doctors informed. Like the paper-based patient record, EPR expresses the rationality of medical science but, unlike the paper-based patient record, the doctors no longer hold a monopoly on the expression of this rationality. The thesis focuses on the spaces of conduct that arise as a result of the managing doctor's political intention to use the transformation of patient record technology as an occasion for managers and professionals to reconsider how they have hitherto organized the routines and tasks in the department.
hdl:10398/7129
Keywords: 650